2020
DOI: 10.1021/acs.analchem.0c00390
|View full text |Cite
|
Sign up to set email alerts
|

Faster and More Specific: Excited-State Intramolecular Proton Transfer-Based Dyes for High-Fidelity Dynamic Imaging of Lipid Droplets within Cells and Tissues

Abstract: Lipid droplets (LDs), a type of dynamic organelle residing at the center of cellular lipid storage, have been identified to play important roles in multiple biological processes, metabolic disorders, and diseases. The highly dynamic characters of LDs were found to correspond to their physiological and pathological functions. Hence, the fluorescent probes which enable dynamic tracking of LDs should be very helpful for better understanding the mechanisms of LDs involved biological processes and diseases. Herein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…21,22 Laser scanning confocal microscopy has been widely used for analyzing luminescence intensity of a probe to construct images, which simply and directly reect the spatial distribution and local concentration of the probe at the subcellular level. 23,24 Once the luminescence intensity of the probe is correlated with its specic interaction with functional biomarkers, luminescence imaging can locate and quantify the marker while continuously monitoring the process of life activities involved in the cell. [25][26][27][28][29] In order to improve the sensing and imaging accuracy and efficiency, it is usually necessary to employ multiple luminophores and simultaneously analyze two or more luminescence signals, thereby allowing one signal to be used as an internal standard, [30][31][32][33] or multiple signals to respond toward different targets.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Laser scanning confocal microscopy has been widely used for analyzing luminescence intensity of a probe to construct images, which simply and directly reect the spatial distribution and local concentration of the probe at the subcellular level. 23,24 Once the luminescence intensity of the probe is correlated with its specic interaction with functional biomarkers, luminescence imaging can locate and quantify the marker while continuously monitoring the process of life activities involved in the cell. [25][26][27][28][29] In order to improve the sensing and imaging accuracy and efficiency, it is usually necessary to employ multiple luminophores and simultaneously analyze two or more luminescence signals, thereby allowing one signal to be used as an internal standard, [30][31][32][33] or multiple signals to respond toward different targets.…”
Section: Introductionmentioning
confidence: 99%
“…15). 34 They screened the derivatives with different p-substituted phenyl groups or furanyls. All these compounds showed strong fluorescence in organic solvents but weak fluorescence in water, accompanied by Stokes shifts over 150 nm.…”
Section: -Hydroxyflavone-based Ld Probesmentioning
confidence: 99%
“…The average size of NLPs was 215.3 nm (Figure 1F). After staining with various neutral lipid dyes [27], all NLPs showed spherical structures, which indicated that they both contained a neutral lipid core (Figure S3).…”
Section: Formation Of Nanolipid Particles and Their Charactersmentioning
confidence: 99%